2008
DOI: 10.1007/s10295-008-0463-1
|View full text |Cite
|
Sign up to set email alerts
|

Production of laccases in submerged process by Pleurotus sajor-caju PS-2001 in relation to carbon and organic nitrogen sources, antifoams and Tween 80

Abstract: Some conditions in media composition for laccases production, such as different sources of carbon and organic nitrogen, antifoams and a surfactant, were studied in liquid cultures of Pleurotus sajor-caju strain PS-2001. Cultivation with fructose or glucose as carbon sources produced maximum enzyme activities of 37 and 36 U mL(-1), respectively. When sucrose was present in the medium, the best results were obtained using 5 g L(-1) of this carbohydrate, on the 11th day of the process, attaining laccase titres of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 49 publications
0
27
0
7
Order By: Relevance
“…Previous studies have shown that Pleurotus sajor-caju strain PS-2001 is able to grow and produce laccase in liquid medium (Confortin et al, 2008;Bettin et al, 2009;Bettin et al, 2011); furthermore, it presents the capacity to reduce phenolic compounds resulting from paper manufacturing and textile dye decolorization (Munari et al, 2007;Munari et al, 2008;Schmitt et al, 2012). The goal of the present study was to obtain higher levels of laccase activity in submerged cultures of P. sajorcaju strain PS-2001 using sucrose from sugar cane, the least expensive source of carbon for bioprocesses, and glucose as carbon source, and several compounds alone or in association, including CuSO 4 , ethanol, and various aromatics: benzoic acid, gallic acid, tannic acid, phenol, syringaldazine, vanillin, and xylidine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that Pleurotus sajor-caju strain PS-2001 is able to grow and produce laccase in liquid medium (Confortin et al, 2008;Bettin et al, 2009;Bettin et al, 2011); furthermore, it presents the capacity to reduce phenolic compounds resulting from paper manufacturing and textile dye decolorization (Munari et al, 2007;Munari et al, 2008;Schmitt et al, 2012). The goal of the present study was to obtain higher levels of laccase activity in submerged cultures of P. sajorcaju strain PS-2001 using sucrose from sugar cane, the least expensive source of carbon for bioprocesses, and glucose as carbon source, and several compounds alone or in association, including CuSO 4 , ethanol, and various aromatics: benzoic acid, gallic acid, tannic acid, phenol, syringaldazine, vanillin, and xylidine.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been conducted to verify the effect of carbon sources on ligninolytic enzyme production by distinct species of basidiomycetes Elisashvili et al, 2006;Revankar and Lele, 2006;Bettin et al, 2009). Laccases can be produced in submerged processes using glucose as the main carbon source and the enzyme titer can be increased by the addition of ethanol (Lee et al, 1999;Rodakiewicz-Nowak 1999), CuSO 4 (Giardina et al, 1999;Palmieri et al, 2000;Baldrian and Gabriel, 2002;Hess et al, 2002;Levin et al, 2002;Chen et al, 2003), gallic acid Peralta et al, 2004;Gnanamani et al, 2006;Revankar and Lele, 2006), tannic acid (Galhaup and Haltrich, 2001), syringaldazine (Koroljova-Skorobogat'ko et al, 1998), vanillin (Peralta et al, 2004;Xiao et al, 2003;Elisashvili et al, 2010), and xylidine (Lee et al, 1999;Elisashvili et al, 2006;Jang et al 2002;Mougin et al, 2002;Kollmann et al, 2005;Pazarlioglu et al, 2005;Jang et al, 2006;Murugesan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This result is not surprising, since most white-rot fungi degrade lignin via oxidation by secreting three enzymes: lignin peroxidase (EC 1.11.1.14), manganese peroxidase (MnP) (EC 1.11.1.13) and laccase (EC 1.10.3.2) [17]. Most species of Pleurotus produce manganese peroxidase and laccase, with high expression levels, in particular for laccase [11,18].…”
Section: Screening and Ligninolytic Activitymentioning
confidence: 99%
“…tryptone, 10 g L -1 yeast extract, 5 g L -1 NH 2 SO 4 and 3 g L -1 NH 4 NO 3 as the nitrogen source) for 16 assays. Sources and concentrations were selected based on optimal results reported in the literature [11,12].…”
Section: Liquid Culturementioning
confidence: 99%
“…In Basidiomycetes, extra-cellular laccases are constitutively produced in small amounts. Laccase expression by fungi is influenced by culture conditions such as the carbon source, carbon-to-nitrogen ratio, pH of the fermentation broth, presence of inducers, and presence of lignocellulose (Bettin et al 2009;Kachlishvili et al 2006;Prasad et al 2004;Revankar and Lele 2006a, b).…”
Section: Introductionmentioning
confidence: 99%